Hand Washing Practice among Secondary School Students in a Rural Area of Bangladesh (Eastern Medical College Journal, 2024)
Background: Human hands play a significant role in the spread of diseases, especially respiratory and diarrheal diseases, which continue to be the leading cause of morbidity and mortality among children worldwide. Hand washing is the most widely used preventive measure to lessen the spread of infectious diseases. It involves washing hands with ordinary or antimicrobial soap and water.  This is especially important for school-age children, since they may be more susceptible to diseases associated with poor hygiene than adults’ age. There is evidence linking the promotion of hand washing habits through health education to a lower incidence of communicable diseases in school-age children. Objectives: To determine the socio-demographic characteristics of the respondents and to find out the practice of hand washing among the secondary school children. Materials & Methods: A cross sectional study was conducted on 340 school students from 1st June 2022 to 30th November 2022 in Alekjan Memorial High School and College, Durgapur, Adarsha Sadar, Cumilla. Purposive sampling was used to gather all pertinent data using a structured questionnaire. Results: In schools, 69.7% of the respondents washed their hands properly. 96.7% of them used soap to wash their hands. About 98.2%, 95%, 86.8%, 82.9% and 80.3% of school children reported that they wash their hands before eating, after using the restroom, after eating, after playing and after working. Conclusion: According to the study, having access to soap and water is necessary for good hand washing technique as the majority of the students used   soap during hand washing.  By installing hand washing stations in schools, the regional government, that is, the education and health bureaus-should enhance the hand washing practices in schools. It is important for parents and other family members to focus more on behavior guidance related to hand washing.Eastern Med Coll J. July 2023; 8 (2): 40-44